The road from Gap Creek [compact disc, unabridged] : a novel - Morgan, Robert, 1944- (HighBridge Audio, 2013)
The Road to Gap Creek takes us back into the lives of Julie and Hank as well as their children, seen through the eyes of their youngest daughter, Annie. Through Annie we watch the four Richards children create their own histories, lives that include both triumph and hardship in the face of the Great Depression and World War II.